2019
DOI: 10.1109/tsm.2019.2897690
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Detection and Segmentation for Wafer Defect Patterns Using Deep Convolutional Encoder–Decoder Neural Network Architectures in Semiconductor Manufacturing

Abstract: Abnormal defect pattern detection plays a key role in preventing yield loss excursion events for the semiconductor manufacturing. We present a method for detecting and segmenting abnormal wafer map defect patterns using deep convolutional encoder-decoder neural network architectures. Using a defect pattern generation model, we create synthetic wafer maps for 8 basis defect patterns, which are used as training, validation, and test datasets. One of the key capabilities for any anomaly detection system is to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…ey used the proportional coefficient of soft shrinkage threshold to optimize DCNN, which was found to be applicable to noise removal in the image [12]. Nakazawa and Kulkarni proposed a method to detect and segment abnormal defect patterns using the NN architecture of deep convolutional encoder-decoder and finally found that these models could detect invisible defect patterns from real images [13].…”
Section: Related Workmentioning
confidence: 99%
“…ey used the proportional coefficient of soft shrinkage threshold to optimize DCNN, which was found to be applicable to noise removal in the image [12]. Nakazawa and Kulkarni proposed a method to detect and segment abnormal defect patterns using the NN architecture of deep convolutional encoder-decoder and finally found that these models could detect invisible defect patterns from real images [13].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, this study does not provide any information about the defect cluster, size and its location. In a later study conducted by the same authors in [107], Nakazawa and Kulkarni overcame the lack of information problem using different type of CNN models such as Fully Convolutional Network (FCN) [402], SegNet [403] and U-Net [404]. These models were compared to each other with regards to their classification performance and training time.…”
Section: Deep Learningmentioning
confidence: 99%
“…Nakazawa and Kulkarni [29] presented SegNet, U-Net, and FCN based autoencoders for detection and segmentation of abnormal wafer map defect patterns. SegNet and U-net based networks showed similar training accuracy, while FCN based architecture performed lower than them.…”
Section: ) Auto_encoder (Ae)mentioning
confidence: 99%